2013
DOI: 10.1158/1535-7163.mct-12-0710
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Temozolomide in Patients with Advanced Aerodigestive Tract and Colorectal Cancers and Methylation of theO6-Methylguanine-DNA Methyltransferase Promoter

Abstract: Responses of patients with gliomas to temozolomide are determined by O 6 -methylguanine-DNA methyltransferase (MGMT) and mismatch repair (MMR) pathways. This phase II study (NCT00423150) investigated whether MGMT promoter methylation predicts response in patients with advanced aerodigestive tract and colorectal cancers (CRC). Tumor and serum samples were screened for MGMT promoter methylation. In methylation-positive patients, 150 mg/m 2 temozolomide was administered daily on a seven-day-on, sevenday-off sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…The MGMT-dependent response to temozolomide-PARPi treatment is also seen in other cancer types To determine whether the impact of MGMT expression on the PARPi response is specific for melanoma cells or cancer type independent, we assessed the response to temozolomide and olaparib in cells from three cancer types where temozolomide is used as a therapeutic option: glioblastoma, pancreatic neuroendocrine tumors (NET), and colorectal carcinoma (11,33,34). We treated seven glioblastoma cell lines (4 MGMT þ and 3 MGMT À cell lines) known to be MMR þ (25) and observed that MGMT expression correlated with the response to temozolomide combined with olaparib ( Fig.…”
Section: Mgmt Is Active In Temozolomide-resistant Cellsmentioning
confidence: 99%
“…The MGMT-dependent response to temozolomide-PARPi treatment is also seen in other cancer types To determine whether the impact of MGMT expression on the PARPi response is specific for melanoma cells or cancer type independent, we assessed the response to temozolomide and olaparib in cells from three cancer types where temozolomide is used as a therapeutic option: glioblastoma, pancreatic neuroendocrine tumors (NET), and colorectal carcinoma (11,33,34). We treated seven glioblastoma cell lines (4 MGMT þ and 3 MGMT À cell lines) known to be MMR þ (25) and observed that MGMT expression correlated with the response to temozolomide combined with olaparib ( Fig.…”
Section: Mgmt Is Active In Temozolomide-resistant Cellsmentioning
confidence: 99%
“…While the trial was still ongoing, four similar phase 2 studies on patients with MGMT -methylated refractory mCRC were published, with conflicting results (Hochhauser et al , 2013; Pietrantonio et al , 2014, 2016; Amatu et al , 2016). Hochhauser et al (2013) reported a disappointing RR of 3% among 31 patients treated with a 7-day-on/7-day-off schedule for each 28-day cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Hochhauser et al (2013) reported a disappointing RR of 3% among 31 patients treated with a 7-day-on/7-day-off schedule for each 28-day cycle. Similarly, Amatu et al (2016) failed to demonstrate a meaningful activity of TMZ, reporting a PFS rate at 12 weeks of 10.3% for 29 patients treated with a standard schedule of TMZ (200 mg m −2 on days 1–5 of 28-day cycles).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations